The Ethnomathematics of the Otonan in the Balinese Calendar System - Gede Ngurah Oka Diputra; Anak Agung Purwa Antara; I Wayan Sudiarta; I Made Yasna; I Gede Bagus Wisnu Bayu Temaja (International Journal of Education, Vocational and Social Science, 2024)
Mathematics and culture are something that cannot be avoided in everyday life. Mathematics and culture are interrelated because mathematics is knowledge humans use to solve everyday problems. In contrast, culture is a complete and comprehensive unity that applies to society. However, sometimes mathematics is seen as outside of everyday life. Ethnomathematics is a mathematical concept that exists in a culture. The presence of mathematics with cultural nuances will make a significant contribution to mathematics learning. One of the ethnomathematics objects in Balinese Hindu culture is the Otonan. Otonan is a birth ceremony carried out by the Balinese people, based on Panca Wara, Sapta Wara, and Wuku in the Balinese calendar system. In determining Otonan, the least common multiple of the numbers 5, 7, 30 and repeated (cycles) are calculated so that the count for the Otonan ceremony is held every 210 days. Meanwhile, in determining Panca Wara, Sapta Wara and Wuku in Otonan, modulo (mod) numbers are used, namely modulo 5, modulo 7 and modulo 30. Ethnomathematics is very important; apart from being a learning material for students, it also functions as a means of cultural preservation.